Lipidomic investigation of eggs' yolk: Changes in lipid profile of eggs from different conditions. (November 2016) - Campos, Ana M.; Ricardo, Fernando; Alves, Eliana; Reis, Ana; Couto, Daniela; Domingues, Pedro; Domingues, M. Rosário M.
Abstract: Eggs are one of the main foods eaten worldwide. Nutritionally they are one of the main sources of dietary lipids, impacting human health. Egg yolk lipid composition changes depending on different conditions associated with hens raising. Therefore, the purpose of our work was to use a lipidomic approach as a tool to evaluate if different diets (vegetable versus animal) and raising environments (free range versus indoor) interfere in the triacylglycerol (TAG) and phospholipid (PL) profiles of eggs' yolks and to use such differences to differentiate eggs according to their origin. To achieve that goal, total lipid extracts were obtained and then fractionated by solid-phase chromatography. TAGs fraction was analysed by ESI-MS and PLs fraction by HILIC-LC-MS/MS. TAG and five PL classes were identified, namely PC, LPC, PE, LPE and SM. Fatty acids (FA) esterified to the glycerol backbone of PL ranged between C16:0 and C22:6. On the other hand, FA esterified to TAG ranged from C14:0 to C20:0. Major differences on the PL profile were observed regarding eggs from free-range hens and fed with vegetable origin food and eggs from the remaining conditions, once the former presented higher levels of PC (O-34:0), PC (34:1) and PE (34:1). Eggs from hens fed with animal origin food contained PL and TAG molecular species richer in n -6 FA, according to GC–MS and to LC-MS/MS data. The lipidomic approach used herein proved to be promising in differentiating eggs from hens with different raising conditions. Graphical abstract: Highlights: Eggs' yolk lipid profile is affected by hens feeding and raising environment Lipidomic approach is a valuable tool to assign eggs depending on hens feed. Eggs from hens fed with vegetable and organic origin food contribute to good n6/n3